Hot acid extraction, characterisation and scavenging activity of pectin from hylocereus polyrhizus - Ahmad Fadzillah, Nurrulhidayah; Othman, Rashidi; Mohd Hassan, Norazian; Muhammad, Nurul Widad Fitri; Abu Bakar, Ainaa Eliah; Noh, Nur Hidayah; Mahmad, Noraini (SET Publisher, 2019)
Gelatin is extensively added to the food products for quality improvements of food entities. The role of gelatin as food thickener, texturizer, stabilizer, ingredient and as an animal based source has restricted its liberal use. However, the usage of this animal-based food quality improver has become less popular due to religious constraints and health restrictions. In fact, it is now direly needed to replace animal-based gelatin by plant-based. Pectin, the basic building material of cell walls in the terrestrial plant has great potential to be gelatin replacer as it can work as a gelling agent, thickener and also a stabilizer. Dragon fruit contains pectin which has high-value functional food as well as health enhancing properties to substitute gelatin’s function in foods production. The current study aims to extract pectin from dragon fruit peels by using hot acid extraction. The optimum conditions for extraction were found to be at 75ºC and pH 3.5 based on the highest percentage of pectin yield (33%). The FTIR result proved that dragon fruit peel contained pectin, which can be used as gelatin replacer are free from any religious and health-wise prohibitions. Pectin extracted was characterized in terms of moisture (14.03 ± 1.925) and ash content (8.73 ± 1.218). The extracted pectin of dragon fruit peel acts as the best gelatin replacer compared to commercial pectin and gelatins from the market. The prepared fruit peels also exhibit high DPPH scavenging activity (57.94%) with methanol extract (2mg/ml).